O viver com o transtorno mental no contexto familiar: abordagem cultural - Rocha, Norma Faustino (2002)
The presente study looks into the consequences that living with a mental disorder may bring to both patients and their families. The research was done through the intensive insertion of the researcher in the cultural context of the informants, adopting concepts from Anthropology as a methodological reference and giving the data a qualitative treatment under an ethnographic perspective. This study describes and highlights the experiences the families of eight mental disorder patients went through during the period that patients were being treated in the same hospital. The focus is on the research domains and taxonomies. Through these categories the theme Living with a mental disorder is difficult was extracted, which represents the cultural knowledge of the informants about the reality that surroundes them. The results point out to the necessity of re-thinking the practice of mental health Services in familiar contexts and of re-focusing these Services, taking into account the diagnoses to be made into familiar and community environments, so that a new health care model can be built according to the sociocultural reality of its target families.